EKSPERIMEN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA DIGITAL NEARPOD BERBASIS CULTURALLY RESPONSIVE TEACHING TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA SMK KELAS XI TAHUN AJARAN 2024/2025 - Pratiwi, Noviana; Bangun Nursanti, Yuli; Kurniawati, Ira; Sujadi, Imam (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
The big challenge faced by our education system, especially in mathematics learning, is the weak learning process. Students are less active in the learning process because the learning strategies applied by teachers in class are still conventional. This study aims to determine the effect of the Problem-Based Learning model assisted by Nearpod digital media based on Culturally Responsive Teaching on students' mathematical literacy skills in the composition function material. The study used a quantitative method with a Quasi-experimental design and a sampling technique, namely cluster random sampling. The research sample was obtained as many as 35 students of XI AKL 1 as the control class and 35 students of XI AKL 3 as the experimental class. The data collection technique used a test method to collect data on students' mathematical literacy skills. This study used a test instrument (pretest-posttest) to measure students' mathematical literacy skills. Data analysis used a normality test and a non-parametric statistical test, namely the Mann-Whitney test. Data processing using Microsoft Office Excel 2019 application and SPSS Statistics 23 Software. Based on the results of the study, it can be concluded that there is a significant difference between classes with the application of the Problem-Based Learning model assisted by Nearpod digital media based on culturally responsive teaching students with the Problem-Based Learning model alone on students' mathematical literacy skills with a significance value of 0.005 <0.05.